A unique noninvasive approach to monitoring dissolved O2 and CO2 in cell culture. Issue 1 (12th September 2014) - Chatterjee, Madhubanti; Ge, Xudong; Uplekar, Shaunak; Kostov, Yordan; Croucher, Leah; Pilli, Manohar; Rao, Govind
ABSTRACT Although online monitoring of dissolved oxygen (DO) and carbon dioxide (DCO2) is highly desirable in bioprocesses, small‐scale bioreactors are usually not monitored due to the lack of suitable sensors. Traditional electrochemical sensors are usually not used because they are bulky and invasive. Disposable optical sensors are small and only partially invasive, but there are concerns regarding the toxicity of the patch and the phototoxicity of the illuminating light. Here we present a novel, noninvasive, rate‐based technique for monitoring DO and DCO2 in cell cultures. A silicone sampling loop which allowed the diffusion of O2 and CO2 through its wall was inserted inside a bioreactor, and then flushed with N2 until the CO2 and O2 inside the loop were completely removed. The gas inside the loop was then allowed to recirculate through gas impermeable tubing to the O2 and CO2 sensors. We have shown that by measuring the initial diffusion rate we were able to determine the partial pressures of the two gases in the culture. The technique could be readily automated and measurements could be made in minutes. It was tested in demonstration experiments by growing murine hybridoma cells in a T‐flask and a spinner‐flask at 37°C. The results were comparable to those measured with commercially available fluorescence‐based patch sensors. These results show that the rate‐based method is an effective way to monitor small‐scale cell cultures. This measurement mechanism can be easily built into disposable cell culture vessels for facile use. Biotechnol. Bioeng. 2015;112: 104–110. © 2014 Wiley Periodicals, Inc.